(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article analyzes the historical formation of international standards of legal ethics based on the study of the law of the Sumerian and Babylonian empires, the first court speeches of ancient Greek and Roman orators, and the influence of Anglo-Saxon legal traditions on the further professionalization of lawyers. The content of individual statements on legal ethics by such well-known figures of the US state and law as Charles Collin, Judson Landon, and John Franklin is examined. The provisions of the Universal Declaration of Human Rights, the Common Code of Conduct for Lawyers of the European Community, and the Charter of Fundamental Principles of the European Legal Profession, which formed the basis of the domestic Rules of Legal Ethics and legal norms regulating the procedural status of a defense attorney in criminal proceedings, are characterized.